Colloid templated semiconductor meta-surface for ultra-broadband solar energy absorber. (1st March 2020) - Liu, Zhengqi; Zhang, Houjiao; Fu, Guolan; Liu, Guiqiang; Liu, Xiaoshan; Yuan, Wen; Xie, Zhiyong; Tang, Chaojun
Graphical abstract: A semiconductor void resonators meta-surface is numerically demonstrated as an ultra-wideband perfect absorber. The spectrally weighted solar energy absorption efficiency is up to 88% in the whole sun irradiation range (280–4000 nm). Highlights: Thin semiconductor void resonators meta-surface has been demonstrated as a feasible way for solar absorber. The spectrally weighted solar energy absorption efficiency is up to 88% in the whole sun irradiation range (280–4000 nm). The findings are desirable for optoelectronic modulators and devices such as infrared detectors and solar absorbers. Abstract: In this work, a thin semiconductor void resonators meta-surface is theoretically proposed and numerically demonstrated as a novel platform for perfect solar absorber. The absorber exhibits an ultra-broadband perfect absorption in the visible and infrared range. In comparison with the noble metals coupled absorbers, it is observed that the introduced titanium substrate produces a strong enhancement (90%) of the spectral absorption for the Ge resonators in a wide spectral window from 1.283 μm to 2.830 μm. As for the actual solar light absorption measurement, the spectrally weighted solar energy absorption efficiency is up to 88% for this semiconductor material based plasmonic absorber in the whole sun irradiation range (280–4000 nm). The absorption behaviors can be artificially manipulated via tuning the structural parameters. Photonic resonant modes in the semiconductor resonators and the plasmonic resonances of the titanium material are the main contributions for the excellent absorption response. In sharp contrast to the metal-insulator absorber, the herein absorber platform can hold three main advantages on the optoelectronic responses by the active semiconductor resonators, the broadband or full-spectrum solar perfect absorption in the semiconductor/titanium composite system, and the stronger thermal stability by the refractory titanium metal.